2005
DOI: 10.1093/carcin/bgi323
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of CWR22Rν1 tumor growth and PSA secretion in athymic nude mice by green and black teas

Abstract: Cancer of the prostate gland (CaP), the most common invasive malignancy and a major cause of cancer related deaths in male population in the USA, is an ideal candidate disease for chemoprevention because it is typically detected in elderly population with a relatively slower rate of growth and progression. Many dietary phytochemicals are showing promising chemopreventive effects, at-least in pre-clinical models of CaP. Our published data in cell culture and animal studies, supported by the work from other labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
61
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 36 publications
8
61
0
Order By: Relevance
“…To examine whether the TAM-stimulated H 2 O 2 is related to a decrease in activity of the mitochondrial enzyme that detoxifies H 2 O 2 , we studied mitochondrial GPx. TAM treatment is reported to reduce the activity of cytoplasmic GPx in rats [23]. We observed that the mitochondrial GPx activity was reduced by TAM.…”
Section: Discussionsupporting
confidence: 48%
“…To examine whether the TAM-stimulated H 2 O 2 is related to a decrease in activity of the mitochondrial enzyme that detoxifies H 2 O 2 , we studied mitochondrial GPx. TAM treatment is reported to reduce the activity of cytoplasmic GPx in rats [23]. We observed that the mitochondrial GPx activity was reduced by TAM.…”
Section: Discussionsupporting
confidence: 48%
“…In addition, black tea extract has recently showed a significant protective effect against testosterone induced oxidative injury in Wistar rat prostate [64]. Significant inhibition in growth of implanted prostate tumors in athymic nude mice and reduction in prostate specific antigen was also recently reported with treatment of water extract of black tea, theaflavins as well as green tea polyphenols [65].…”
Section: Animal Model Studies On Tea and Prostate Cancermentioning
confidence: 93%
“…Protein extraction and western blotting Protein lysates from cultured cells were prepared, 40 mg protein was subjected to SDS-polyacrylamide gel electrophoresis (PAGE) and western blot was performed as previously described (Siddiqui et al, 2006). The extraction of tumor proteins from TRAMP mice has been described previously (Adhami et al, 2004).…”
Section: Methodsmentioning
confidence: 99%